Optimization of Control Self Assessment Application to Minimize Fraud - Wendy Endrianto (Binus Business Review, 2016)
This article discussed a method that can be done by a company to minimize fraud action by applying Control Self Assessment (CSA). The study was conducted by studying literature on the topics discussed that were presented descriptively in a systematic manner through the review one by one from the initial problem to solve the problem. It can be concluded that CSA is one form of auditing practices that emphasizes anticipatory action (preventive) of the act of detection (detective) that the concept of modern internal audit which is carried more precise in application. It is one alternative that is most efficient and effective in reducing fraud.